2005
DOI: 10.1111/j.1399-5618.2005.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder in children and adolescents: international perspective on epidemiology and phenomenology

Abstract: Relative lack of data, ICD-10 and DSM-IV differences in diagnostic criteria, different levels of recognition of Child and Adolescent Psychiatry as a true specialty in Europe, clinician bias against BD, an overdiagnosis of the disorder in USA and/or a true higher prevalence of pediatric BD in USA may explain these results. US-International differences may be a methodological artifact and research is needed in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 51 publications
3
62
0
9
Order By: Relevance
“…Clinical samples have revealed prevalence estimates ranging from 1.7 to 4.2%. 39 In Brazil, a study found 36 subjects with pediatric BD (PBD; , 15 years old) in a sample of 500 patients from a child and adolescent psychopharmacology outpatient program. 40 These data combined suggest the prevalence of BD type I and II in children and adolescents to be between 0.1 to 2.5%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Clinical samples have revealed prevalence estimates ranging from 1.7 to 4.2%. 39 In Brazil, a study found 36 subjects with pediatric BD (PBD; , 15 years old) in a sample of 500 patients from a child and adolescent psychopharmacology outpatient program. 40 These data combined suggest the prevalence of BD type I and II in children and adolescents to be between 0.1 to 2.5%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Tanı dağılımına bakıldığında, bir çocuk ve ergen psikiyatri polikliniğinde BPB tanı-sı alanlar üzerinde yapılan bir çalışmada BPB-I için %48, BPB-II için %16, başka türlü adlandırılamayan BPB (BPB-BTA) için %36 bulunmuştur (Soutullo 2003). Son dö-nemde yapılan bir çalışmada ise BPB tanısı alanların %44.7'si BPB-I, %5.3'ü BPB-II ve %50'si BPB-BTA olarak ayrıştırılmıştır (Escamilla ve ark.…”
Section: Poliklinik öRneklemlerindeunclassified
“…Axelson ve arkadaşlarının (2006), hastanede yatan ve/veya ayaktan takipli 7-18 yaş arası 438 bipolar çocuk ve ergen üzerinde yaptığı araştırmada, hastalığın başlama yaşı sırasıyla BPB-I için 9.5 (± 4.0) yıl, BPB-II için 11.2 (± 3.4) yıl ve BPB-BTA için 8.7 (± 3.5) yıl olarak bulunmuştur. Ancak, hastaların belirtilerinin başlama-sından ortalama 4.4 yıl sonra tanı aldıkları belirlenmiştir (Soutullo 2003). Başka bir çalışmada ise BPB tedavisi alan çocuk ve ergenlerin yarısından fazlasının belirtilerin ortaya çıkmasından en az 5 yıl sonra bir tanı aldığı bulunmuştur (Marchand ve ark.…”
Section: Başlama Yaşıunclassified
See 1 more Smart Citation
“…3 Considering bipolar spectrum disorders, from 4 to 18% of children and adolescents referred to psychiatric evaluations satisfy the criteria for those disorders. 4 Attention-deficit/hyperactivity disorder (ADHD) is present in about 5% of children and adolescents across different cultures. 5 High rates of comorbidity between ADHD and BD are observed in childhood (over 60%), especially in clinical samples.…”
Section: Introductionmentioning
confidence: 99%